Legitimacy and the European Union : the contested polity - Banchoff, Thomas F., 1964-; Smith, Mitchell P., 1960- (London ; New York : Routledge, 1999)
Beetham and Lord provide concise and analytical coverage of a key topic within the European Union, that is, the legitimacy of European supra-national governance.
Most of the contemporary debates about the European Union - about its role, its institutional arrangements, its development dynamic, its expansion and possible futures - revolve around the issue of political legitimacy. Legitimacy and the European Union addresses the fundamental issues at the heart of the debates on Europe and examines such key questions as:- -What is the scope of the EU's authority -Is there a legitimacy deficit? If so, how much does it matter -Does political legitimacy only reside in the nation state? Using a multi-dimensional conception of political legitimacy, the text analyses the character and problems of the European Union's authority in respect of democracy, political identity and governmental performance. Its distinctive claim is that political legitimacy can now only be understood as a process of interaction between the state and EU levels, and that this interaction impacts differentially on different member states.
Introduction: conceptualizing legitimacy in a contested policy / Thomas Banchoff and Mitchell P. Smith -- EU legitimacy and the "defensive" reaction to the single European market / Mitchell P. Smith -- Unity-in-diversity: cultural policy and EU legitimacy / Melissa Pantel -- Reconciliation and legitimacy: foreign relations and enlargement of the European Union / Lil Gardner Feldman -- Political parties and the problem of legitimacy in the European Union / Robert Ladrech -- National parties and the contestation of Europe / Gary Marks and Carole Wilson -- The European parliament and EU legitimacy / Wolfgang Wessels and Udo Diedrichs -- EU citizenship: implications for identity and legitimacy / Rey Koslowski -- National identity and EU legitimacy in France and Germany / Thomas Banchoff -- Political rhetoric and the legitimation of the European Union / John Gaffney.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: European Union; European Union; Union européenne.; European federation; Legitimacy of governments -- Europe; Union européenne.; Légitimité des gouvernements -- Europe; Construction européenne.; LAW -- International; European federation; Legitimacy of governments; Europe; Competence; European Union; Legitimacy; Democracy; Political parties; European integration; Community law; Légitimité des gouvernements -- Europe; Partis politiques et Union européenne.; Europe de l'Ouest -- Unité.